Consequences of Security Breaches to Print-Information Resources and Preventive Measures in Public Libraries of North Western Nigeria - Madaki,, A. S.; Yakasai,, U. U. (Kashere Journal of Education, 2021)
This study examined consequences of security breaches to information resources and preventive measures in public libraries of North-Western Nigeria. Quantitative research methodology through cross sectional survey design was employed for the study, the design was adopted for its opportunity of allowing data to be collected at one point in time. The population of the study were 145 library staff of the readers’ services departments of the seven public libraries’ headquarters in the North West geo-political zone. Data were collected through questionnaire, using simple random sample. Descriptive statistics using frequency percentages through the use of SPSS 16.0 versions were used for data analysis. The study revealed that majority of the information resources mostly affected by security issues are printed resources. And that the major security breaches in the libraries are inadequacy of security personnel, scarcity of library materials, Poor arrangement of library materials, poor environmental condition, unsecured environment, juvenile users, disasters, among others. It also revealed that information availability, information accessibility and use and information resources development as the major consequences of security breaches in libraries.